Características da assistência ao trabalho de parto e parto em três modelos de atenção no SUS, no Município de Belo Horizonte, Minas Gerais, Brasil Characteristics of labor and delivery care in three healthcare models within the Unified National Health System in Belo Horizonte, Minas Gerais State, Brazil - Sibylle Emilie Vogt; Simone Grilo Diniz; Carlos Mendes Tavares; Nagela Cristine Pinheiros Santos; Camilla Alexsandra Schneck; Bianca Zorzam; Débora de Andrade Vieira; Kátia Silveira da Silva; Marcos Augusto Bastos Dias (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
Estudo transversal com 831 gestantes, de risco habitual, sobre o manejo do trabalho de parto num Centro de Parto Normal (CPN), num hospital vencedor do título "Galba de Araújo" (HG) e numa maternidade com modelo assistencial prevalente (HP). O uso da ocitocina no CPN foi de 27,9%, no HG 59,5% e no HP 40,1%, enquanto a amniotomia foi realizada em 67,6%, 73,6% e 82,2% das mulheres, respectivamente. A realização da episiotomia foi menor nas modalidades com incorporação de práticas humanizadas: 7,2% no CPN e 14,8% no HG versus 54,9% no HP. A prática de oferta liberal no HG resultou numa taxa de analgesia superior (54,4%) à do HP (7,7%). O percentual de internação dos recém-nascidos e o de parto a fórceps foram mais altas no HP, mas não houve diferenças para o índice de Apgar e para a taxa de cesárea. Os resultados sugerem resistência ao uso seletivo de intervenções em todos os modelos assistenciais, embora favoreçam o CPN como estratégia no controle das intervenções durante o trabalho de parto e parto nas gestantes de risco habitual sem prejuízos para as mulheres e os recém-nascidos. This cross-sectional study of 831 low-risk pregnancies compared the management of labor and delivery in a birthing center, a hospital that had previously won the "Galba de Araújo" Award (for excellence in obstetric and neonatal care), and a standard-protocol maternity facility. The rates for use of ocytocin during labor were 27.9%, 59.5%, and 40.1%, while amniotomy was performed in 67.6%, 73.6%, and 82.2% of the women, respectively. Episiotomy rates were lower in the first two facilities, which have adopted patient-centered obstetric practices (7.2% at the birthing center and 14.8% at the award-winning hospital) as compared to 54.9% at the standard maternity facility. The liberal offer of epidural anesthesia at the awarding-winning hospital resulted in a higher anesthesia rate (54.4%) as compared to the standard facility (7.7%). Forceps delivery and neonatal admission rates were higher in the standard hospital, but there were no differences in mean Apgar or cesarean rates. The findings suggest resistance to selective use of interventions in all three models of obstetric care, although favoring the birthing center as a strategy for controlling interventions during labor and childbirth in low-risk pregnancies, with no resulting harm to the mothers or newborns.